Organizational citizenship behavior role in mediating the effect of transformational leadership on organizational performance in gold industry of Saudi Arabia - Alhashedi, Aref Abdulkarem Ali; Bardai, Barjoyai; Al-Dubai, Maged M. Mahyoub; Alaghbari, Mohammed Abdulrazzaq (Business: Theory and Practice, 2021)
This paper mainly aims at investigating the mediating effect of organizational citizenship behaviour in the relationship between transformational leadership behaviour and organizational performance as well as the mediating effect of organizational citizenship behaviour in the relationship between psychological ownership, working environment, employee involvement, incentives, and employee motivation, and organizational performance. To achieve the objectives of the study, quantitative research approach was applied through a questionnaire specifically designed to collect primary information from the samples of the study, which consisted of (250) managers in gold shops in Jaddah. The collected data was analysed using SPSS 20.0 and Smart-PLS 3. The results showed that organization citizenship behaviour mediates the relationship between transformational leadership behaviour, psychological ownership and incentives, and organizational performance in the Saudi Arabian gold industry. Also, organization citizenship behaviour has no mediating effect on the relationship between working environment, employee involvement, employee motivation, and organizational performance in the Saudi Arabian gold industry. At the end of this study, the researcher recommended the need to encouraging the practice of organizational citizenship behaviours by developing a set of special regulations and instructions, and consider organizational citizenship behaviours as one of the important criteria in the annual performance appraisal models for employees, in addition to that, the quantitative method was adopted in this research to test research hypotheses, thus, future studies can rely on other methods qualitative or case study to verify the results of this research.